ANALIS DATA PENGUNJUNG MALL LIPPO CIKARANG PADA BULAN JUNI 2024 - Adeta Suci Anggraini; Ariadil Pulungan; Devia Wulandari; Fajar Setiawan; Mochamad Malik Yassin Supriyadi; Nashwa Mutiara Putri; Naufal Munfarid; Miftakul Huda (Kajian Ekonomi dan Akuntansi Terapan, 2024)
This study aims to analyze the characteristics and behavior of visitors to Lippo Cikarang Mall, focusing on demographics, shopping preferences, and satisfaction levels with the facilities and services provided. Efforts to increase the volume of visitors to find out: the number of visitor respondents, the number of respondents who filled out the questionnaire and the statistics of the crowd of visitors. Data was collected through a survey involving 70 respondents who were randomly selected in various areas of the mall. Descriptive statistical analysis is used to describe visitor profiles, while inferential analysis is applied to identify factors that affect customer satisfaction. The results of the study show that the majority of visitors are in the age group of 15-55 years old with an upper-middle-income income. Shopping preferences are more dominant on fashion and food products. The level of visitor satisfaction is high, especially regarding cleanliness, safety, and tenant variety, but there are complaints related to limited parking spaces. This finding provides valuable insights for the management of Lippo Cikarang Mall in formulating strategies to improve services and a better shopping experience for visitors